2015
DOI: 10.1186/s40550-015-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin residue and their impact on biomolecules in eggs of laying hens following oral administration

Abstract: Background: The present study was designed to evaluate Ciprofloxacin residue and their impact on some biomolecules (albumin, total protein and cholesterol) in eggs of laying hens after oral administration. For that purpose, One group (A) of laying hens (n = 20) were orally administered 10 mg⁄kg ciprofloxacin for five consecutive days. The second group (n = 10) was untreated controls. Eggs were collected from day one of treatment and up to 25 days after withdrawal of treatment. Egg white and yolk from each egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Animal derived food contains natural bacteriostatic substances, which can inhibit the growth of microorganism in microbiological kits and result in false positive results ( Gaudin et al, 2013 ; Billah et al, 2015 ). In this study, the method of pre-permeation at RT was used to prevent excessive natural bacteriostatic substances in animal food from permeating through the kit’s medium.…”
Section: Discussionmentioning
confidence: 99%
“…Animal derived food contains natural bacteriostatic substances, which can inhibit the growth of microorganism in microbiological kits and result in false positive results ( Gaudin et al, 2013 ; Billah et al, 2015 ). In this study, the method of pre-permeation at RT was used to prevent excessive natural bacteriostatic substances in animal food from permeating through the kit’s medium.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, in Cameroon, Guetiya Wadoum et al [ 25 ] demonstrated the presence of chloramphenicol and tetracycline residues in concentrations above the maximum residue limit (MRL) recommended by the European Union in 2010, in edible chicken tissues (muscle, gizzards, heart, liver, kidney) and eggs. Similarly, Billah et al [ 24 ] detected ciprofloxacin in higher concentration in egg white, but in lower concentration in egg yolk during treatment of the birds. Also, Olufemi and Agboola [ 76 ] reported a high oxytetracycline residue in edible beef tissues of cattle slaughtered at Akure, in Nigeria, at violating levels beyond the MRL stipulated by WHO.…”
Section: Antibiotics In Agriculturementioning
confidence: 91%
“…Antibiotics have been reported to accumulate and form residues at varying concentrations in the tissues and organs of food animals, as presented in Table 1 . Billah et al [ 24 ] referred to these antibiotic residues as chemical residues or pharmacologically active substances representing either the parent compound or its degraded products, which are released, gathered, or stored in the edible tissues of the animal, due to their use in the prevention, treatment, and control of animal diseases. Undoubtedly, in Cameroon, Guetiya Wadoum et al [ 25 ] demonstrated the presence of chloramphenicol and tetracycline residues in concentrations above the maximum residue limit (MRL) recommended by the European Union in 2010, in edible chicken tissues (muscle, gizzards, heart, liver, kidney) and eggs.…”
Section: Antibiotics In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…In both white and yolk, concentrations increased during a five days treatment period. After withdrawal of treatment, eight days and fourteen days were required to deplete the drug residue below the established LOD in albumen and yolk respectively (Billah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%